Effect of texture parameters on cutting performance of flank-faced textured carbide tools in dry cutting of green Al2O3 ceramics. Issue 11 (1st August 2018) - Liu, Yayun; Deng, Jianxin; Wang, Wei; Duan, Ran; Meng, Rong; Ge, Dongliang; Li, Xuemu
Abstract: Tool wear and surface quality are the most important problems in green ceramic processing. This paper fabricated textures with different texture parameters on the flank face of carbide tools by femtosecond laser, to enhance the wear resistance of carbide tools and surface quality of machined compacts. The wear resistance of textured tools and quality of machined surface were evaluated in cutting tests of the green Al2 O3 ceramics with these different flank-faced textured tools. Results showed that better flank wear resistance of textured tools and better quality of machined surfaces could be obtained by flank-faced textured tools than that by conventional tool (WT-0). The parameters of flank-faced textures had a significant effect on the flank wear resistance of textured tools and surface quality of machined workpieces. To achieve best wear resistance of cutting tool and surface quality of workpieces within the experiment parameters, the best parameters of the textures were chosen that width of the texture groove was 75 µm, spacing of texture groove was 100 µm, and distance of texture groove to main cutting edge was 75 µm. "Derivative cutting" to the hard inclusions in the surface of workpieces was happened at the textured grooves' lower edge. It contributed to enhancement of wear resistance and the surface quality in a certain parameter of texture grooves.